2012
DOI: 10.1210/en.2011-1260
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin Signaling Is Indispensable for Neurokinin B, but not Glutamate, Stimulation of Gonadotropin Secretion in Mice

Abstract: Kisspeptins (Kp), products of the Kiss1 gene that act via Gpr54 to potently stimulate GnRH secretion, operate as mediators of other regulatory signals of the gonadotropic axis. Mouse models of Gpr54 and/or Kiss1 inactivation have been used to address the contribution of Kp in the central control of gonadotropin secretion; yet, phenotypic and hormonal differences have been detected among the transgenic lines available. We report here a series of neuroendocrine analyses in male mice of a novel Gpr54 knockout (KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
139
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(163 citation statements)
references
References 52 publications
20
139
3
1
Order By: Relevance
“…Of note, the stimulatory effects of senktide on LH secretion were abrogated in Gpr54 null mice, thus suggesting that these require the integrity of kisspeptin signaling to manifest (35), a contention that is also supported by recent findings in the monkey (36). Notwithstanding these solid pharmacological data, evidence for null or even inhibitory responses to NKB agonists has also been presented (37,38).…”
Section: Kisspeptins: Major Gatekeepers Of Pubertymentioning
confidence: 81%
See 2 more Smart Citations
“…Of note, the stimulatory effects of senktide on LH secretion were abrogated in Gpr54 null mice, thus suggesting that these require the integrity of kisspeptin signaling to manifest (35), a contention that is also supported by recent findings in the monkey (36). Notwithstanding these solid pharmacological data, evidence for null or even inhibitory responses to NKB agonists has also been presented (37,38).…”
Section: Kisspeptins: Major Gatekeepers Of Pubertymentioning
confidence: 81%
“…In keeping with the hypogonadotropic phenotype of patients with inactivating mutations of the NKB system, a number of studies in ewes, monkeys, mice, and rats have documented stimulatory actions of the NKB agonist, senktide, on LH secretion (28,33,34,35). Of note, the stimulatory effects of senktide on LH secretion were abrogated in Gpr54 null mice, thus suggesting that these require the integrity of kisspeptin signaling to manifest (35), a contention that is also supported by recent findings in the monkey (36).…”
Section: Kisspeptins: Major Gatekeepers Of Pubertymentioning
confidence: 94%
See 1 more Smart Citation
“…Physiologically, GALP administration was shown to stimulate LH release in mice (Kauffman et al 2005), which occurs in a kisspeptin-independent manner (Garcia-Galiano et al 2012), and GALP infusion was sufficient to rescue the onset of puberty in food-restricted weanling male and female rats (Mohr et al 2012), demonstrating GALP is modulated by nutritional signals and also facilitates fertility in vivo. Accordingly, rats exhibiting insulin-dependent diabetes have reduced Galp mRNA compared to control animals, and brain insulin administration reversed this effect .…”
Section: Galp-expressing Neuronsmentioning
confidence: 96%
“…As reviewed by Iremonger and coworkers (Iremonger et al 2010), many studies have shown that glutamate agonists and antagonists injected into the brain can stimulate or inhibit LH secretion, respectively (Lopez et al 1990, Brann & Mahesh 1995, Ping et al 1997. Glutamate likely exerts its influence via direct effects on GNRH neurons, as TenaSempere's lab demonstrated that glutamate-stimulated LH secretion occurs in a kisspeptin-independent manner (Garcia-Galiano et al 2012). Furthermore, neurons in the ventral premamillary nucleus (PMV) of the hypothalamus, which mediate some of leptin's metabolic influences on GNRH function (Donato et al 2011), are almost exclusively glutamatergic (Kocsis et al 2003), supporting a role for glutamate-expressing neurons in the metabolic control of fertility.…”
Section: Glutamate-expressing Neuronsmentioning
confidence: 99%